Evaluation of antimicrobial efficacy of an herbal preparation vs triple antibiotic paste against E. faecalis: an in vitro study - Dhyani, Chandni; Chaudhry, Kalpna; Khanduri, Nitin; Pradhan, Leina R.; Gupta, Yoshita (International Journal of Contemporary Pediatrics, 2026)
Background: Enterococcus faecalis is a major pathogen responsible for persistent endodontic infections and root canal treatment failure due to its resistance and ability to survive harsh intracanal conditions. Triple antibiotic paste (TAP) is widely used for canal disinfection, but concerns related to antibiotic resistance, tooth discoloration, and cytotoxicity have led to interest in herbal alternatives. This study evaluated the antimicrobial efficacy of a herbal formulation containing Turmeric, Arjuna bark and Clove oil, against E. faecalis and compared it with TAP. Methods: An in vitro well diffusion assay was performed using E. faecalis (ATCC 29212) inoculated on Mueller–Hinton agar. Three concentrations (20 mg/ml, 50 mg/ml, and 100 mg/ml) of the herbal extract were tested, and zones of inhibition (ZOI) were measured after incubation at 37°C for 48 hours. Minimum inhibitory concentration (MIC) was determined using a microbroth dilution method. TAP served as the positive control. Results: The herbal preparation demonstrated measurable antimicrobial activity, showing a ZOI of 8 mm (20 mg/ml), 10 mm (50 mg/ml), and 15 mm (100 mg/ml). The MIC value for the herbal formulation was 7.81 µg/ml. TAP showed higher inhibition zones at all tested concentrations. Conclusions: The herbal formulation exhibited significant antibacterial activity against E. faecalis, indicating its potential as a biocompatible intracanal medicament. Although TAP remained more effective at lower concentrations, the herbal preparation offers advantages such as reduced risk of antibiotic resistance and tooth discoloration. Further cytotoxicity testing and clinical studies are required to validate its clinical applicability.